Discrete improvement in racial disparity in survival among patients with stage IV colorectal cancer: a 21-year population-based analysis - Castleberry, Anthony W.; Güller, U.; Tarantino, Ignazio; Berry, M. F.; Brügger, L.; Warschkow, R.; Cerny, T.; Mantyh, C. R.; Candinas, D.; Worni, M. (Journal of gastrointestinal surgery, 2014)
Recently, multiple clinical trials have demonstrated improved outcomes in patients with metastatic colorectal cancer. This study investigated if the improved survival is race dependent.
Gesehen am 21.08.2020